A Proton Magnetic Resonance Spectroscopic Study in Autism Spectrum Disorder Using a 3-Tesla Clinical Magnetic Resonance Imaging (MRI) System: The Anterior Cingulate Cortex and the Left Cerebellum. (July 2017) - Ito, Hiromichi; Mori, Kenji; Harada, Masafumi; Hisaoka, Sonoka; Toda, Yoshihiro; Mori, Tatsuo; Goji, Aya; Abe, Yoko; Miyazaki, Masahito; Kagami, Shoji
The pathophysiology of autism spectrum disorder (ASD) is not fully understood. We used proton magnetic resonance spectroscopy to investigate metabolite concentration ratios in the anterior cingulate cortex and left cerebellum in ASD. In the ACC and left cerebellum studies, the ASD group and intelligence quotient- and age-matched control group consisted of 112 and 114 subjects and 65 and 45 subjects, respectively. In the ASD group, γ-aminobutyric acid (GABA)+/ creatine/phosphocreatine (Cr) was significantly decreased in the anterior cingulate cortex, and glutamate (Glu)/Cr was significantly increased and GABA+/Cr was significantly decreased in the left cerebellum compared to those in the control group. In addition, both groups showed negative correlations between Glu/Cr and GABA+/Cr in the left cerebellum, and positive correlations between GABA+/Cr in the anterior cingulate cortex and left cerebellum. ASD subjects have hypoGABAergic alterations in the anterior cingulate cortex and hyperglutamatergic/hypoGABAergic alterations in the left cerebellum.